Case Report: New Application of a Gufoni Maneuver Variation for Apogeotropic Lateral Semicircular Canal Benign Paroxysmal Positional Vertigo - Jiaoxuan Dong; Ling Li; Songbin He; Haipeng Liu; Fangyu Dai (Frontiers in Neurology, 2022)
BackgroundSeveral canalith repositioning procedures (CRPs) such as Gufoni maneuver have been proposed to treat the apogeotropic lateral semicircular canal variant of BPPV (LC-BPPV). The reported success rate varied widely in different studies. Research showed that there was a risk of treatment failure due to insufficient repositioning of the debris. So far, there is insufficient evidence to recommend a preferable CRP for apogeotropic LC-BPPV.Case descriptionA 49-year-old woman and a 48-year-old man diagnosed with apogeotropic LC-BPPV relapse were treated with original Gufoni maneuver for apogeotropic variant but no satisfactory result was obtained. A variation of Gufoni maneuver originally proposed for the geotropic variant was applied to detach otoconia toward the utricle or the non-ampullary arm. Apogeotropic nystagmus was successfully transformed into the geotropic variant. The subsequent Gufoni maneuver was successful. On a 64-year-old male with untreated apogeotropic LC-BPPV, we performed the Gufoni maneuver variation and observed a change in nystagmus direction. In all the three cases, no relapse of vertigo was reported after 1 month.ConclusionThe new application of Gufoni maneuver variation may improve the treatment of apogeotropic LC-BPPV. Treatment efficacy and patient-specific optimization such as head rotation angle deserve a large-scale validation and further investigation.